Characterization of resistant starch from Se‐rich rice flour and its anti‐diabetic effect in diabetic ICR mice. (12th October 2015) - Yuan, Huaibo; Wang, Wenjuan; Chen, Deyi; Zhu, Xiping; Cao, Shuqing
Abstract : Resistant starch (RS) in Se‐rich rice flour was enhanced by autoclaving and debranching modification. The morphological, crystalline and thermal properties and the in vitro hydrolysis rate of the RS product were analyzed. The RS‐enhanced Se‐rich rice (SR‐RS) was investigated as functional food with a beneficial effect on type 2 diabetes. The effects of SR‐RS on the body weight (BW), fasting blood glucose levels (FBG), serum lipids and insulin (SIN) levels of normal and diabetic mice were investigated. The results of scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and X‐ray diffraction (XRD) analyses confirmed that retrogradation and recrystallization improved the structural and thermal stabilities of RS‐enhanced Se‐rich rice flour. Additionally, the SR‐RS showed a lower in vitro hydrolysis rate than SRF due to its high RS content. Moreover, results from the animal experiment showed SR‐RS have a significant anti‐diabetic effect based on the lower BW, FBG levels, SIN and lipid contents of diabetic mice treated with SR‐RS compared to the diabetic control mice.